Development of Small and Medium Entrepreneurship in the Republic Of Croatia - Ivana Radlović; Anica Hunjet; Goran Kozina (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Entrepreneurship is a key driver of economic growth and a generator of employment opportunities in all modern economies across the world. Small and medium enterprises (SMEs) are the engines of modern entrepreneurship. In the Republic of Croatia, SMEs are also indispensable in the effort to boost employment and economic growth. The global economic crisis has virtually brought the national economies worldwide to a halt, causing a considerable decline in production, consumption, and gross domestic product. In such conditions, the development of individual entrepreneurial competencies and entrepreneurial culture represents the main preconditions for successful economic growth and development. The SME sector plays a key role in achieving this by increasing the national economy's competitiveness in the regional and European Union markets. The aim of this paper is to present the position of entrepreneurs in the Republic of Croatia, to identify challenges that come with setting up a business, and to describe the state of small and medium entrepreneurship in the Republic of Croatia.
Keywords: L26; O10; 330; entrepreneurship; small business; Republic of Croatia; economic development; European Union